Evaluación de las dimensiones culturales de los Proyectos Educativos Institucionales y Proyectos Curriculares del Centro 1 - Sara -Lafosse, Mercedes Giesecke (2007)
This working paper has been discussed with the headmasters and teachers of six schools in Huaycan. It includes some features of their own Institutional Educational Projects that combined with this papers concepts and their own experiences can be instrumental for them to carry out a situation analysis of the cultural policies that they are implicitly or explicitly promoting. The paper concludes with some questions for reflection.